Diagnostic performance of 18F-PSMA-1007 PET/CT in patients with biochemical recurrent prostate cancer - Rahbar, Kambiz; Afshar-Oromieh, Ali (European journal of nuclear medicine and molecular imaging, 2018)
PurposeThe introduction of ligands targeting prostate-specific membrane antigen (PSMA), especially 68Ga-PSMA-11, has changed the management of patients with prostate cancer (PCa). 18F-Labelled ligands can be produced in larger amounts and therefore can improve availability for a larger group of patients. The aim of this study was to evaluate the diagnostic performance of the recently introduced 18F-PSMA-1007 in patients with recurrent PCa.MethodsThis retrospective analysis included 100 consecutive patients with biochemical relapse (mean age 68.75 ± 7.6 years) referred for PSMA PET/CT. Whole-body PET/CT imaging (from the lower limbs to the skull) was performed in all patients 120 min after injection of 338 ± 44.31 MBq 18F-PSMA-1007. Prostatectomy, radiation beam therapy of the prostate bed and androgen-deprivation therapy had been performed in 92%, 45% and 27% of the patients, respectively. Radiation beam therapy of the prostate bed had been performed in addition to surgery in 38 patients (38%) and 10 patients (10%) had received all three therapy modalities. The probability of a 18F-PSMA-1007 PET/CT scan suggestive of pathology was compared with the Gleason score (GS) and PSA level.ResultsOf the 100 patients, 95 (95%) showed at least one pathological finding on 18F-PSMA-1007 PET/CT. The overall median PSA level was 1.34 ng/ml (range 0,04-41.3 ng/ml). The rates of pathological scans were 86%, 89%, 100% and 100% among patients with PSA levels ≤0.5, 0.51-1.0, 1.1-2.0 and > 2.0 ng/ml, respectively. The median GS was 7 (range 5-10). The majority of patients (70) with a GS available had a score in the range 7-9. The rate of pathological scans in these patients was 93% (65/70). The median SUVmax values of the pathological findings were 10.25, 14.32, 13.16 and 28.87 in patients with PSA levels ≤0.5, 0.51-1.0, 1.1-2.0 and >2.0 ng/ml, respectively. The median SUVmax in patients with a PSA level of >2.0 ng/ml was significantly higher than in all other PSA groups.Conclusion18F-PSMA-1007 PET/CT can detect recurrent PCa in a high percentage of patients with biochemical relapse. The probability of a pathological 18F-PSMA-1007 PET/CT scan seems to be high even in patients with a low PSA level ≤0.5 ng/ml, and this may have a significant impact on the management of this relevant group of patients.
Im Titel ist die 18 hochgestellt
Gesehen am 27.03.2019